Accountability in Village Owned Enterprises (BUMDes) Based on Sustainable Livelihood Assets - Amerieska, Siti; Andhayani, Atik; Nugrahani, Novi (Journal of International Conference Proceedings, 2021)
The number of fraud cases in Village-Owned Enterprises (BUMDes) necessitates the implementation of accountability in order to reduce the potential for corruption or other forms of fraud within the BUMDes entity. Meanwhile, research on accountability in BUM Desa has received little attention. This paper aims to study an accountability model based on Sustainable Livelihood Assets, which include accountability based on asset potential (natural, physical, financial, human, social and cultural assets) that has been institutionalized in the management of BUMDes. This study uses a descriptive qualitative approach with content analysis method and as theoretical triangulation also uses data in the form of interviews with BUMDes directors and staff, village heads, and the community. The result Legal, policy, and compliance accountability for aspects of governance is the main foundation for complying with the regulations set in BUMDes, which states that BUMDes problems in their management are required elements of prudence that prioritize transparency and accountability. Managerial Accountability that emphasis in the managerial aspect is on how to embed the institutional elements of BUMDes that are patterned on administration, reporting, and accountability. It is possible that the procedural system for managing BUMDes includes several aspects such as social for institutional strengthening, the transformation of the environment into management, and the development of BUMDes.